PENGARUH PENAMBAHAN LIMBAH SERBUK BATA MERAH DAN LIMBAH TEMPURUNG KELAPA TERHADAP KUAT TEKAN BETON - Nurjanah Nurjanah; Hazairin Nikmatul Nikmatul (Universitas Islam Balitar Blitar, 2020)
In Blitar City, the use of coconuts from trees to fruit is increasing rapidly, from tree trunks that can be used for wooden horses, to the fruit which can also be used as various kinds of food and crafts. The growth of trade in handicrafts made from coconut shells, waste from craftsmen can also be used as additional material for making concrete because coconut shells contain a lot of chemicals. Not only coconut shell waste can be used in the manufacture of innovative building materials, but also red brick powder obtained from demolition of residential buildings and unused buildings. To prove and determine the effect of the addition of red brick powder and coconut shell waste, therefore the concrete compressive strength test used 24 samples consisting of normal concrete and 3 variations of red brick powder and coconut shell waste ranging from 3%, 6% and 9 %. So the results of normal concrete aged 14 days with a compressive strength of 19.42 MPa, so there is an increase of 20.02 MPa in the 3% mixture. Then there is a decrease in the amount of 16.53 MPa in the 6% mixture, and there is another increase in the mixture of 9%, which is worth 19.06 MPa. And at the age of 28 days the average is the same at the amount of 20.0 MPa and the mixture is 9%. the value of 19.45 MPa.